Significant Impact of Promoter Hypermethylation and the 540 C>T Polymorphism of CDKN2A in Cutaneous Melanoma of the Vertical Growth Phase - Straume, Oddbjørn (American Society for Investigative Pathology, 2002)
Promoter hypermethylation, mutations, and loss of heterozygosity in the CDKN2A gene as well as polymorphisms at the 3′-untranslated region were determined in vertical growth phase melanomas. Methylation-specific polymerase chain reaction in soluti and in situ showed that 19% of the cases were hypermethylated at the CDKN2A promoter region, and some of these cases were heterogeneous with both methylated and unmethylated tumor cells. Methylation was associated with increased tumor cell proliferation by Ki-67 expression (P = 0.01) and decreased patient survival (P = 0.025). Point mutations in CDKN2A were found in 4% of the cases, whereas 90% had loss of heterozygosity at one or more of 4 markers studied. Furthermore, presence of the 540 C>T polymorphism at the 3′-untranslated region of CDKN2A (23%) was associated with improved survival in multivariate analysis (hazard ratio, 2.6; P = 0.02). Our results suggest that promoter methylation of the CDKN2A gene is present in a subgroup of the tumors and associated with increased tumor cell proliferation and reduced survival. Further, the 540 C>T polymorphism might define a distinct subgroup of low-grade vertical growth phase melanomas. These findings support a significant role of the CDKN2A gene in melanoma progression.